Pencegahan Anemia Untuk Menurunkan Angka Stunting Berbasis Aplikasi Android Fikes-BlesD di SMA Dr. Soetomo Surabaya - Arkha Rosyaria Badrus; Nurul Fathiyyah; Kholifatul Ummah; Alief Ayu Purwitasari (Rena Cipta Mandiri, 2026)
Low reproductive health literacy and a high risk of anemia among adolescents demand sustainable educational interventions. The partner (SMA Dr. Soetomo) has implemented regular health checks and anemia screening; however, these activities are time-limited, do not yet allow for independent screening, and lack digital media support for control and monitoring by the school or health workers. The educational application